Incorporation of Chitosan and Glass Substrate for Improvement on Adsorption, Separation and Stability of Tio2 Photocatalysis - Amir, Muhammad Nur Iman; Julkapli, Nurhidayatullaili Muhd; Hamid, Sharifah Bee Abd (International Journal of Natural Sciences Research, 2016)
It has been demonstrated that the single TiO2 has high capabilites for photodegradation process for all types pollutants. However, TiO2 are still far from becoming a potential candidate for photocatalytic system due to weakness for the adsorbtion process, separation as well as dissolution during the treatment. Therefore, this study highlights on the highly adsorption, easy separation and promising stability of TiO2(SY) photocatalyst by fabrication of Chitosan-TiO2(SY) supported glass substrate (Cs-TiO2(SY)/Glass substrate) photocatalysts. Cs with abundant R-NH and NH2 groups promotes adsorption sites of synthetic dyes. Meanwhile, present of glass substrate support increase the stability and easy separation of the potocatalysts. The fabrication process Cs- TiO2(SY)/Glass substrate has been done through dip-coating methods. Further analyzed by the adsorption photodegradation with Methyl Orange (MO) as a model of synthetic dyes compound. Approximately, 70% of total removal of MO by optimize 8 layers of photocatalyst analysis has been achieved within 1 hour of UV irradiation. Besides that, the adsorption photocatalyst has been achieved about 50% when no exposure of light for 15 minutes irradiation. It concluded that, a suitable photocatalytic conditions and sample parameters, possessing the Cs-TiO2(SY) gave the benefits of adsorption-photodegradation practice in the abatement of wastewater contaminants.